Petrology and Geochemistry of Gole Pillow Basalt in Penjween area Kurdistan Region- NE Iraq - Jabbar M. A. Qaradaghi; Yousif O. Mohammed; Salim A. Aziz. (Tikrit Journal of Pure Science)
The petrological, morphometric and geochemical analyses of pillow lava from Gole village (Penjween town) Sulaimani city Northeastern Iraq have been undertaken. The Gole Pillow basalt (GPB) extruded, in the form of pillow and sheet flow into the Qulqula radiolarite Formation. The basaltic intrusion restricted to a small area of about 100 m2 within Penjween- Walash zone in the Zagros Suture Zone (ZSZ) of Iraq. The investigated area divided into two sections GPB1 and GPB2. It is envisaged that the studied area distinct two episodes of submarine alkaline eruptions that produced pillowed lavas that differently interacted with seawater to produce different morphologies and geochemistries. The pillows of the GPB1 section well exposed all along the Shalair river near Gole village. Although the pillows of the GPB2 section altered due to low-grade metamorphism and late hydrothermal processes, their igneous textures are still preserved. GPB samples are mostly phyric in nature and show porphyritic or sub-ophitic textures.